2012
DOI: 10.1002/asna.201111589
|View full text |Cite
|
Sign up to set email alerts
|

The absorption and emission spectrum of the magnetic Herbig Ae star HD 190073

Abstract: We determine abundances from the absorption spectrum of the magnetic Herbig Ae star HD 190073 (V1295 Aql). The observations are primarily from HARPS spectra obtained at a single epoch. We accept arguments that the presence of numerous emission lines does not vitiate a classical abundance analysis, though it likely reduces the achievable accuracy. Most abundances are closely solar, but several elements show departures of a factor of two to three, as an earlier study has also shown. We present quantitative measu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…This may represent the development of chemical peculiarities over time during the pre-main sequence, however a larger sample size is needed to draw firm conclusions. These results agree well with the work of Cowley et al (2010) who independently found λ Boo peculiarities in HD 101412, and Cowley & Hubrig (2012) who found solar abundances in HD 190073. Cowley et al (2013) and Cowley et al (in press) report an additional chemically normal HAeBe star and a λ Boo HAeBe star, further supporting the very high incidence of λ Boo peculiarities among HAeBe stars.…”
Section: Discussionsupporting
confidence: 92%
“…This may represent the development of chemical peculiarities over time during the pre-main sequence, however a larger sample size is needed to draw firm conclusions. These results agree well with the work of Cowley et al (2010) who independently found λ Boo peculiarities in HD 101412, and Cowley & Hubrig (2012) who found solar abundances in HD 190073. Cowley et al (2013) and Cowley et al (in press) report an additional chemically normal HAeBe star and a λ Boo HAeBe star, further supporting the very high incidence of λ Boo peculiarities among HAeBe stars.…”
Section: Discussionsupporting
confidence: 92%
“…The absorption and emission spectrum of the Herbig Ae star HD 190073 was studied in detail by Catala et al (2007) and more recently by Cowley & Hubrig (2012). The low projected rotational velocity (v sin i ≤ 9 km s −1 ) may indicate either a very slow rotation, or a very small inclination of the rotation axis with respect to the line of sight.…”
Section: Hd 190073mentioning
confidence: 99%
“…The absorption and emission spectrum of the Herbig Ae/Be star HD 190073 was studied in detail by Catala et al (2007) and more recently by Cowley & Hubrig (2012). The low projected rotational velocity (v sin i ≤ 9 km s −1 ) may indicate either a very slow rotation, or a very small inclination of the rotation axis with respect to the line of sight.…”
Section: Reduction Of Harps Spectra and Notes On The Samplementioning
confidence: 99%